Monocrystal CsSnBr3 micron sheet as well as preparation method and application thereof

Single-crystal CsSnBr3 microsheets were prepared by using non-toxic tin ions instead of lead ions, which solved the problem of toxic lead in existing perovskite micro/nano lasers, and achieved the preparation of high-quality lead-free single-crystal perovskite echo wall mode micro-nano lasers.

CN119615358APending Publication Date: 2025-03-14JILIN UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411717930.9
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-28
Publication Date
2025-03-14

AI Technical Summary

Technical Problem

The existing perovskite micro/nano lasers contain toxic lead ions, which limits their large-scale production and commercial expansion in the field of micro/nano lasers.

Method used

Single-crystal CsSnBr3 micron sheets were prepared by using non-toxic metal tin (Sn) cations instead of lead ions.

Benefits of technology

The prepared single crystal CsSnBr3 microsheets exhibit echo wall mode resonance at 313K above room temperature, with a threshold of 181.3 μJ/cm2, with good optical performance and lasing behavior, and are suitable for the development of lead-free single crystal perovskite echo wall mode micro-nano lasers.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119615358A_ABST
    Figure CN119615358A_ABST
Patent Text Reader

Abstract

The invention provides a single crystal CsSnBr3 micron sheet and a preparation method and application thereof, and relates to the field of perovskite micro / nano lasers. According to the preparation method, cesium bromide and tin bromide powder are used as precursors, a single-crystal CsSnBr3 micron sheet is grown through high-temperature vapor phase epitaxy, and the side length of the single-crystal CsSnBr3 micron sheet ranges from 6 micrometers to 12 micrometers. The prepared single crystal CsSnBr3 micron sheet can be used as a gain medium and an optical microcavity for preparing a lead-free single crystal perovskite echo wall mode micro-nano laser; in addition, the material has intrinsic fluorescent light emission at the wavelength of about 685nm, and can be used as a gain medium of a near-infrared micro / nano laser; the micron sheet shows a lasing behavior at room temperature and also has a lasing behavior at 313K, the laser threshold value at room temperature is 122.5 mu J / cm < 2 >, and the micron sheet can be used for developing environment-friendly and biological-friendly photoelectric devices in the field of room-temperature laser, and is used for preparing small lasers; the method has the advantages of non-toxic raw materials, simplicity in operation, low cost, no need of a catalyst, environment friendliness and the like.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of perovskite micro / nano lasers, and in particular to a single crystal CsSnBr3 micron sheet and a preparation method and application thereof. Background Art

[0002] Lasers are widely used in biosensors, microscopy, laser surgery, optical computing, information storage, nanoanalysis and other fields. Micro / nano lasers have attracted wide attention as coherent light sources in photonic integrated circuits. Perovskite materials can achieve wide-band adjustable laser output, ultraviolet band, full visible spectrum, infrared and other wavelength outputs that are difficult to obtain by adjusting the bandgap width, luminescence spectrum range and optical properties.

[0003] It has been reported that amplified spontaneous emission (ASE) was successfully observed in MAPbI3 perovskite films obtained by solution processing. The organic-inorganic hybrid perovskite sheets prepared by chemical vapor deposition achieved a low laser threshold at room temperature. The lead halide perovskite nanowires prepared by the low-temperature solution method showed an ultra-low laser threshold at the nanocoke scale. In addition, high-quality up-conversion single-mode laser emission was achieved in a single CsPbBr3 microcube perovskite, and it can still remain stable at an operating temperature of up to 440K.

[0004] Most perovskite materials contain metallic lead ions. However, the toxicity of lead can cause damage to the environment and organisms, and this unfavorable factor has seriously restricted its large-scale production and commercial expansion in the field of micro / nano lasers. The development of tin-based perovskite materials with lasing emission characteristics can effectively resolve the toxicity problem of lead. There have been related reports showing that CsSnI3 prepared by low-temperature solution method and treated with SnF2, with the help of natural photonic crystals in butterfly wings, successfully achieved feedback lasing at near-infrared wavelengths; organic-inorganic hybrid perovskite FASnI3 films were found to have random laser phenomena in a low-temperature environment of 20K, and inorganic CsSnI3 films were found to have random laser phenomena in a room temperature environment.

[0005] Although amplified spontaneous emission (ASE) has been observed in CsSnBr3 micropyramids, no Sn-based perovskite micro-nanolasers resonating in single-crystal cavity structures, such as nanowires, nanorods, microplates, and micropyramids, have been reported so far. Summary of the invention

[0006] In order to solve the above technical problems, the present invention replaces toxic lead (Pb) cations with non-toxic metal tin (Sn) cations, and provides a single crystal CsSnBr3 micron sheet and its preparation method and application.

[0007] The single crystal CsSnBr3 micron sheet of the present invention comprises the following steps:

[0008] Slowly send the processed Si / SiO2 substrate into the tubular furnace body and place it in the center of the second temperature zone of the tubular furnace;

[0009] Weigh two precursor powders of cesium bromide (CsBr) and tin bromide (SnBr2) in a molar ratio of 1:1, grind the two precursor powders fully and put them into a quartz boat; slowly send the quartz boat into the center of the first temperature zone in the tubular furnace;

[0010] Turn on the mechanical pump and continuously introduce nitrogen into the tube furnace to remove moisture, air and other impurities in the tube furnace;

[0011] The precursor was heated to 450°C at a rate of 15°C / min and heated to 5.0×10 -1 Keep warm at Pa for 10-15min;

[0012] Heat the three temperature zones of the tube furnace to 750°C, 415°C, and 415°C respectively, and maintain them for 30-40 minutes. Control the pressure in the furnace to 60-80 Torr and the argon gas flow rate to 200-300 sccm.

[0013] After the reaction is completed, the substrate is taken out after the temperature in the quartz boat drops to room temperature, and single crystal CsSnBr3 micron sheets are generated on the substrate.

[0014] Furthermore, the processing of the Si / SiO2 substrate includes:

[0015] Use a natural diamond silicon wafer knife to cut the Si / SiO2 wafer into square substrates, use nitrogen to blow away the debris on the surface of the substrate, put it into deionized water, sonicate it in an ultrasonicator for 30 minutes, then put it into anhydrous ethanol and sonicate it in an ultrasonicator for 30 minutes. Repeat the above operation three times; take out the substrate and clean the remaining liquid on the substrate with low-flow nitrogen.

[0016] Furthermore, the mass purity of the cesium bromide (CsBr) powder is not less than 99.9%, the mass purity of the tin bromide (SnBr2) powder is not less than 99%; the mass purity of the nitrogen and argon gases is not less than 99.999%.

[0017] Furthermore, the pressure in the controlled furnace is preferably 75 Torr and the argon flow rate is 200 sccm.

[0018] The high-quality single-crystal CsSnBr3 micron sheet prepared by the present invention exhibits whispering gallery mode (WGM) resonance at 313K above room temperature, with a threshold of 181.3 μJ / cm 2, indicating that the present invention prepares a single crystal whispering gallery mode lead-free cesium tin halide perovskite microcavity, which can be used to prepare lead-free single crystal perovskite whispering gallery mode micro-nano lasers, to develop environmentally and bio-friendly optoelectronic devices in the field of room temperature lasers, and to prepare small lasers.

[0019] Beneficial effects of the present invention:

[0020] The present invention uses cesium bromide and tin bromide powder as precursors and utilizes high temperature vapor phase epitaxy to grow single crystal CsSnBr3 micron sheets, whose side length is in the range of 6 to 12 μm. The method for growing the prepared single crystal CsSnBr3 micron sheets has the advantages of non-toxic raw materials, simple operation, low cost, no need for catalysts, and environmentally friendly, and the prepared micron sheets have high purity and good optical properties at room temperature; the single crystal CsSnBr3 micron sheets prepared by the present invention can be used as a gain medium and an optical microcavity to prepare a lead-free single crystal perovskite whispering gallery mode micro-nano laser; and it has intrinsic fluorescence at a wavelength of about 685 nm, and can be used as a gain medium for near-infrared micro / nano lasers; in addition to exhibiting lasing behavior at room temperature, it also has lasing behavior at 313 K, and the laser behavior in the temperature range of 193 to 313 K is mainly dominated by excitons, and the laser threshold at room temperature is 122.5 μJ / cm 2 , the characteristic temperature that characterizes the temperature stability of the laser is 75.02 K. The optical image of the single crystal CsSnBr3 micron sheet shows that the morphology is a square micron sheet. The single crystal CsSnBr3 micron sheet perovskite has excellent geometry, crystal structure and optical properties, and can be used to develop environmentally and biologically friendly optoelectronic devices in the field of room temperature lasers and to prepare small lasers; it has potential application value for lead-free tin-based inorganic perovskites in optoelectronic applications and the development of micro-nano lasers. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 It is a schematic diagram of the structure of the growth equipment for preparing samples of the present invention.

[0022] Figure 2 It is an optical photograph of the whole sample prepared by the present invention.

[0023] Figure 3 This is a SEM image of a single CsSnBr3 micron sheet prepared by the present invention.

[0024] Figure 4 It is a schematic diagram of the optical path for testing the optical properties of the sample of the present invention.

[0025] 1. Sample, 2. Objective lens, 3. Dichroic mirror, 4. Beam splitter, 5. Convex lens, 6. Camera, 7. Spectrometer, 8. Laser.

[0026] Figure 5 This is the spectrum diagram of the single-piece CsSnBr3 micron sheet of the present invention.

[0027] Figure 6 This is the room temperature laser spectrum of the single CsSnBr3 micron sheet of the present invention.

[0028] Figure 7 It is the power-dependent lasing spectrum of the single CsSnBr3 micron sheet of the present invention. DETAILED DESCRIPTION

[0029] Embodiment 1,

[0030] The method for preparing a single crystal CsSnBr3 micron sheet provided in this embodiment is as follows:

[0031] (1) Processing of Si / SiO2 substrate:

[0032] Use a natural diamond silicon wafer knife to cut the Si / SiO2 wafer into 1×1 cm square substrates, clamp the substrate with tweezers, use nitrogen to blow away the debris on the surface of the substrate, put it into the silicon wafer cleaning rack, put the cleaning rack into a beaker, slowly pour in deionized water until the substrate is covered, put it into an ultrasonic instrument for ultrasonication for 30 minutes, take out the cleaning rack, replace the liquid in the beaker with anhydrous ethanol, put the cleaning rack into the beaker until the substrate is covered, and ultrasonicate it in the ultrasonic instrument for 30 minutes. Repeat the above operation three times; take out the cleaning rack, clamp the substrate out with tweezers, and use low-flow nitrogen to clean the remaining liquid on the substrate.

[0033] (2) Preparation of single crystal CsSnBr3 micron sheets:

[0034] The treated Si / SiO2 substrate was slowly introduced into the tube furnace and placed 20 cm downstream of the quartz boat, i.e., at the center of the second temperature zone of the tube furnace. Two precursor powders of cesium bromide (CsBr) and tin bromide (SnBr2) were weighed at a molar ratio of 1:1, with weights of 21.28 mg and 27.85 mg, respectively. The two precursor powders were fully finely ground and placed in the quartz boat. The quartz boat was slowly introduced into the center of the first temperature zone of the tube furnace. The mechanical pump was turned on to continuously introduce nitrogen into the tube furnace to remove moisture, air and other impurities in the tube furnace. The precursor was heated to 450°C at a rate of 15°C / min and heated to 5.0×10 -1 Pa for 10 min; the temperatures of the three temperature zones of the tube furnace are heated to 750°C, 415°C, and 415°C, respectively, and maintained for 30 min, and the pressure in the furnace is controlled by a computer to be 75 Torr and the argon gas flow rate is 200 sccm; after the reaction is completed, the sample is taken out after the temperature in the quartz boat drops to room temperature, and a single crystal CsSnBr3 micron sheet is obtained on a Si / SiO2 substrate.

[0035] The mass purity of the cesium bromide (CsBr) powder is 99.9%, the mass purity of the tin bromide (SnBr2) powder is 99%; the mass purity of the nitrogen and argon gases is 99.999%.

[0036] Figure 1 It is a schematic diagram of the structure of the single crystal CsSnBr3 micron sheet preparation equipment.

[0037] To further confirm the sample morphology, the whole sample and the separated single micron flakes were characterized respectively. Figure 2 is an optical photograph of the entire sample, Figure 3 This is a SEM image of a single CsSnBr3 micron sheet. From the image, we can see that the sample surface is smooth and uniform, and the edges are straight and sharp.

[0038] The CsSnBr3 micron sheet prepared by the present invention is measured by X-ray diffraction (XRD). According to ICSD-4071, the diffraction peak can be marked as a cubic CsSnBr3 perovskite structure. There is no other signal except CsSnBr3, indicating that the single crystal micron sheet has high crystal quality purity.

[0039] Embodiment 2,

[0040] Characterization of optical properties of single crystal CsSnBr3 microsheets at room temperature.

[0041] Using a pulsed laser with a wavelength of 343nm as the excitation light, a frequency of 250KHz, and a pulse width of 236fs, the sample single crystal CsSnBr3 micron sheet was optically tested, and parameters such as the photoluminescence spectrum (PL) and time-resolved photoluminescence spectrum (TRPL) were analyzed to characterize its optical properties. Figure 4 This is a schematic diagram of the optical path of the spectrum test equipment. A laser with a wavelength of 343nm is used as the pump light source, and a 10× ultraviolet objective lens is used to focus the laser on the sample. The spot size is about 25μm. The backscattered signal enters the spectrometer and CCD through the objective lens for collection and processing to obtain the corresponding spectrum, and the optical photo of the sample is taken with a camera.

[0042] Figure 5 The fluorescence spectrum of the sample is given. Under the excitation of 343nm laser, the single CsSnBr3 micron sheet grown in this example emits intrinsic fluorescence at a wavelength of about 685nm. The horizontal axis represents the wavelength and the vertical axis represents the relative intensity.

[0043] Using an ultraviolet objective lens, a 343nm pulsed laser is irradiated onto a single CsSnBr3 micron sheet, and a very bright red spot appears. By further increasing the excitation power and measuring the spectrum of the sample, the lasing spectrum is obtained, as shown in Figure 6As shown in the figure, the horizontal axis represents wavelength and the vertical axis represents relative intensity. When the excitation power is low, the sample emits weak fluorescence due to spontaneous radiation, the spectrum is smooth, and the fluorescence peak is about 685nm; as the excitation power increases, the sample fluorescence continues to increase. When the excitation light reaches a certain intensity, some sharp laser narrow peaks begin to appear, and the intensity of the spontaneous radiation area is close to saturation, such as Figure 7 As shown, it is equivalent to the transition from spontaneous radiation to stimulated radiation. The inset proves that the resonance mode is the whispering gallery mode. It shows that the synthesized CsSnBr3 has a high gain coefficient and has broad application prospects in the field of room temperature lasers.

Claims

1. A method for preparing single crystal CsSnBr3 micron sheets, characterized in that: The following steps are involved: Place the processed Si / SiO2 substrate in the center of the second temperature zone in the tubular furnace; Weigh two precursor powders of cesium bromide and tin bromide in a molar ratio of 1:1, grind the two precursor powders fully and put them into a quartz boat; place the quartz boat in the center of the first temperature zone in the tubular furnace; Turn on the mechanical pump and continuously introduce nitrogen into the tube furnace to remove moisture, air and other impurities in the tube furnace; The precursor was heated to 450°C at a rate of 15°C / min and heated to 5.0×10 -1 Keep warm at Pa for 10-15min; Heat the three temperature zones of the tube furnace to 750°C, 415°C, and 415°C respectively, and maintain them for 30-40 minutes. Control the pressure in the furnace to 60-80 Torr and the argon gas flow rate to 200-300 sccm. After the reaction is completed, the substrate is taken out after the temperature in the quartz boat drops to room temperature, and single crystal CsSnBr3 micron sheets are generated on the substrate.

2. The method for preparing a single crystal CsSnBr3 micron sheet according to claim 1, characterized in that: The processing process of the Si / SiO2 substrate includes: Use a natural diamond silicon wafer knife to cut the Si / SiO2 wafer into square substrates, use nitrogen to blow away the debris on the surface of the substrate, put it into deionized water, sonicate it in an ultrasonicator for 30 minutes, then put it into anhydrous ethanol and sonicate it in an ultrasonicator for 30 minutes. Repeat the above operation three times; take out the substrate and clean the remaining liquid on the substrate with low-flow nitrogen.

3. The method for preparing a single crystal CsSnBr3 micron sheet according to claim 1, characterized in that: The mass purity of the cesium bromide powder is not less than 99.9%, and the mass purity of the tin bromide powder is not less than 99%; the mass purity of the nitrogen and argon is not less than 99.999%.

4. The method for preparing a single crystal CsSnBr3 micron sheet according to claim 1, characterized in that: The center of the first temperature zone is 20 cm away from the center of the second temperature zone, that is, the substrate is located 20 cm downstream of the quartz boat.

5. The method for preparing a single crystal CsSnBr3 micron sheet according to claim 1, characterized in that: The pressure in the furnace was controlled to be 75 Torr and the argon flow rate was 200 sccm.

6. A single crystal CsSnBr3 micron sheet, characterized in that: The preparation method according to any one of claims 1 to 4 is a single crystal lead-free CsSnBr3 perovskite microcavity with a side length in the range of 6 to 12 μm.

7. The use of a single crystal CsSnBr3 micron sheet according to claim 6, characterized in that: It can be used as a gain medium and optical microcavity to prepare lead-free single crystal perovskite whispering gallery mode micro-nano lasers.

8. The use of a single crystal CsSnBr3 micron sheet according to claim 6, characterized in that: Used to develop environmentally and bio-friendly optoelectronic devices in the field of room temperature lasers and to prepare small lasers.

9. The use of a single crystal CsSnBr3 micron sheet according to claim 6, characterized in that: It has intrinsic fluorescence at a wavelength of 685nm and can be used as a gain medium for near-infrared micro / nano lasers.